STUDY OF Cr(VI) PHOTOREDUCTION CATALYZED BY CDO-ZEOLITE - Endang Tri Wahyuni; Mudasir Mudasir; Saudur Sinambela (Indonesian Journal of Chemistry, 2002)
An attempt to decrease Cr(VI) ions in the solution which is more toxic than Cr(III) has performed by assisting the photoreduction of Cr(VI) ions catalysed by oxide Cd(II) supported in the zeolite pores (CdO-zeolite). The research consists of preparation, characterization, and photoactivity examination of  CdO-zeolite. The preparation was carried out by ion-exchange method, which was followed by oxidation by flowing oxygen gas at 300oC. Analysis to determine the Cd adsorbed by zeolite and characterization to determine Eg as photocatalyst character was carried out by AAS and diffuses reflectance UV-Visible spectrophotometry (DRUV-Vis) methods, respectively. Photoreduction process was carried out in a closed reactor by radiating a suspension of Cr(VI) solution and CdO-zeolite with UV lamp for period of times. The concentration of unreduced Cr(VI) in the solution was determined by UV-Visible spectrophotometer as biphenyl carbacide complex. The results of the analysis and characterization indicated that the amount of Cd in  CdO-zeolite is 46,832 mg/g and  Eg of CdO-zeolite (3,26 eV) is larger than Eg of CdO (2,38 eV). Photocatalytic examination showed that the photoreduction results are proportional with the Eg values,i.e the results of  Cr(VI) catalyzed by CdO-zeolit are higher than that of by  CdO. Photoreduction of  50 mL solution  Cr(VI) 25 ppm at  pH = 7 catalyzed by  50 mg CdO- zeolite for 25 hours has given maximum result of 65,89 %.